The Effect of Learning Methods Discovery Learning Model Based on Animated Video Media on Skills Writing Text - Sri Mulyani Rusli; Febrina Riska Putri (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The current learning model uses more digital technology to support efficiency. One of them is the Discovery Learning model which is assisted by the ability to write expository texts using animated video media. The purpose of this study was to find out, based on the results of several researchers, whether the discovery learning model is supported by the environment. The method that the author uses is Systematic Literature Review (SLR), the reviewed articles are obtained from several sources, namely the National Library, Science Direct and also Google Scholar which discusses the Discovery learning model and explanatory texts. The research begins with the collection of literature related to the research topic. The results of this study show that with this students can write expository texts better by applying the form of learning and combining it with the learning environment.